The role of alcohol and substance usage history in committed suicides - Ekici, Gıyaseddin; Savaş, Haluk A.; Çıtak, Serhat (Journal of Dependence, 2001)
Object: It is thought that one forth of all attempted suicides are related with alcohol usage.Alcohol dependence is the second important factor increasing the tendency to suicide in later phases of human life. On the other side its verifiedthat heroin addicts have greater risk for suicide than controls. In present study we aimed to determine frequency of alcohol and substance usage in committed suicides.Method: Between the dates 1.1.1996-31.6.1997 police files are reviewed about committed suicides in İstanbul. And then the persons in that list are looked for whether they were treated in Bakırköy Mental Hospital. The files of persons committed suicide who were treated there(n=48) are surveyed about alcohol and substance usage with the aid of a semi-structured form. A matched group who didn’t commit suicide but have same first axis diagnosis, same gender and age used as control group(n=45). Possible relation with the alcohol-subs-tance usage, clinical and socio-demographic variables are studied retrospectively.Results:Alcohol usage is found to be more frequent in suicide group as compared to the control group. Alcohol usage at level of abuse or dependence is found to be %35.4 in the suicide and % 15.6 in the control groups. With the same criteria drug-substance usage is found %2.1 in the suicide group % 2.2 in the control group, and mixed usage of alcohol-subs-tance-drug is found % 14.6 in the suicide group and % 13.3 in the control groups respectively.Conclusion: Alcohol abuse or dependence are risk factors increasing the possibility of suicides in our country more than substance usage. These results also suggest that we should be more cautious and focus on alcohol usage problems in psychiatric patients to consider the increasing risk of suicide.
Keywords: Alcohol abuse; substance abuse; suicide